Identifying the Cause of Chocolate Spot (Botrytis fabae) Disease on Faba Bean Leaves in Al-Marj and Al-Wasitah regions in Al-Jabel Al-Akhdar - Mohamed, Nwara Ali; Bouazzoum, Noura Mohammed (Al-Mukhtar Journal of Sciences, 2021)
This study aimed to identify the fungus that causes chocolate spot disease on bean leaves. Bean leaves were collected randomly from fields in Al-Marj and Al-Wasitah regions during February and March 2017 in late flowering and fruiting stages, showing symptoms of disease 50 plants/field. The infection rate and severity of the samples were estimated. The pathogen of chocolate spot disease was isolated from naturally infected leaves. After testing its pathogenicity, the pure fungus was grown on solid food media that included both Zapex (Cz) and potato dextrose agar (PDA) and environment malt agar (MA) and incubated at 22 Celsius.The results of the study showed that the bean leaves grown in the fields of both Al-Marj and Al-Wasitah were infected with chocolate spot disease, as its symptoms appeared in the form of small reddish-brown spots on the leaves with an average diameter of 0.52 cm. The severity of the disease was recorded by calculating the infection rate, and it reached 87.6% in Al-Marj fields, while the severity of infection was higher in Al-Wasila fields, reaching 49.7%. The study also confirmed the ability of the pure fungus isolated from bean leaves to infect and record the stain on the leaves of the Egyptian bean plant 48 hours after injection. It became clear through the measurements that the pathogen responsible for the disease is the fungus Botrytis fabae, characterized by dark divided mycelium, its thickness (average of 11.75 micrometers), and its production of conidia bacteria in clusters at the ends of a branched-chain, which are single-celled, round, light brown in color, average length 14.5 micrometers and width 10.8 micrometers. Also, the Zapex environment gave the highest growth of mycelium, germs, and microsclerotia compared to other nutritional media.